Calculation of Cost of Rice Production in Farmer Groups Source of Fortune in Sidomukti Village, Muara Kaman District, Kutai Kartanegara Regency - Yuliyasari, Tri; Mansyur, Mansyur; Sanjaya, Arwin (Jurnal Indonesia Sosial Sains, 2023)
This research aims to determine the calculation of the cost of rice production of the Source of Fortune Farmer Group in Sidomukti Village, Muara Kaman District, Kutai Kartanegara Regency. This type of research is descriptive qualitative, aims to describe, describe, explain and provide answers more clearly about the problem under study. Primary data from the results of the study were obtained from interviews and then analyzed by the full costing method. The number of respondents in this study was 19 people who were members of the Sumber Rejeki Farmer Group with their own land status. The results of this study show that the calculation of the cost of goods produced for an area of 0<x≤1 ha is Rp. 3,608,-/kg, land area 1<X≤2 ha amounting to Rp. 3,857,-/ kg and for land area x>2 ha. Rp. 4.198,-/kg. Production costs for a land area of 0<x≤1 ha average Rp. 12,244,400, an average land area of 1<X≤2 of Rp. 12,971,222, and an average land area of x>2 ha of Rp. 13. 649.429. The calculation is obtained from the process of entering raw material costs, direct labor costs, ovearhead costs. The cost of goods produced is generated from the cost of raw materials which include rice seeds, fertilizers and pesticides. Labor costs which include costs for tillage, seeding, planting, fertilizing, maintenance, harvesting and post-harvest and overhead costs include equipment rent, land and building taxes, depreciation and other costs.